2021
DOI: 10.3390/ijerph18063138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mandate Contract and Self-Employment on Workers’ Health—Evidence from Poland

Abstract: The purpose of the study is to analyze the correlations between two clearly defined forms of non-standard employment (self-employment and mandate contract) and workers’ health. The study also addressed such variables as gender, age, length of service, and the reason for employment (voluntary vs. non-voluntary). The research was carried out in Poland in 2020 using the CATI method (a telephone interviewing technique), and it covered a sample of 200 workers (100 self-employed and 100 working under a mandate contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Only in the case of contracts of mandate and its impact on the employers’ investments in C4 and C6 was there confirmation of the statements, previously published in the literature on the subject, that the low employability of workers in non-standard FoEs is related to employers’ investing less in their development (Bernstrøm et al. , 2019; Piwowar-Sulej and Bąk-Grabowska, 2021).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Only in the case of contracts of mandate and its impact on the employers’ investments in C4 and C6 was there confirmation of the statements, previously published in the literature on the subject, that the low employability of workers in non-standard FoEs is related to employers’ investing less in their development (Bernstrøm et al. , 2019; Piwowar-Sulej and Bąk-Grabowska, 2021).…”
Section: Discussionmentioning
confidence: 74%
“…Third, previous studies showed that people who worked based on a contract of mandate were identified as representatives of the precariat, found themselves in a much worse situation. They were less educated at the start, the contract of mandate was more often an involuntary FoE for them (Piwowar-Sulej and Bąk-Grabowska, 2021). However, this study clearly demonstrated that in the case of 6 out of 14 competencies not only FoE and education level but also other factors such as respondents’ age (physical health-related training), parental status (foreign languages courses) and industry played an important role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berkowitz showed that self-employed workers were more likely to be uncovered by health insurance [29]. A Polish study concluded that there were different types of health gaps between self-employed and employed workers, which was reflected in the self-employed workers were more vulnerable to mental health but the employed workers more vulnerable to physical health [30]. Searson, on the other hand, discussed that the health differences between immigrants and non-immigrants [31].…”
Section: Introductionmentioning
confidence: 99%